Activating/Mobilizing Intersectional Assets: Racial Justice-Focused School Leadership Systems That Center Students of Color and Privilege Their Interests - Ung-Sang Albert Lee (Education Sciences)
Integrating Students of Color in school leadership offers ways to remediate the historical exclusion of Students of Color from schooling, develop asset-based educational practices for Students of Color, and offer rich developmental pathways for the students. Efforts to build more participatory leadership systems must consider how the unique assets that Students of Color bring to bear are positioned and leveraged within such leadership systems, the kinds of structures and practices that facilitate the meaningful participation of Students of Color in school leadership, and how the interests of Students of Color are privileged through their participation in school leadership. This paper examines three student cases that analyze the students’ participation in efforts aimed at centering students in conceptualizing, designing, and implementing digital media-integrated school practices. The analysis will show that a diverse set of student assets, such as their families’ political activism, career aspirations shaped by experiences with literature across borders, and experiences with navigating tensions across multiple axes of exclusion, helped the students navigate their emergent roles in school leadership. Such asset-based participation led to the activation/mobilization of such assets towards the students’ broader life and educational goals. Together, their experiences can help inform the ways we build asset-based, racial justice-focused school leadership systems that facilitate the meaningful participation of Students of Color.